2018
DOI: 10.1002/hed.25381
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐mesenchymal transition and microRNAs: Challenges and future perspectives in oral cancer

Abstract: Therefore, we propose that targeting therapies to epithelial-mesenchymal transition-type cells, namely, coordinating microRNAs and/or hydrophobic drugs, such as conventional therapy, could be a promising strategy to improve the outcomes of patients with OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…The angiogenesis of tumors can be controlled by miRNAs such as miR-210 and miR-519c under hypoxic conditions via modulating Hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) 78 . Regulatory networks of miRNAs are considered to be a characteristic of epithelial-mesenchymal transition (EMT) in the physiopathology of OSCC 79 . An aggressive phenotype of colorectal cancer (CRC) is significantly associated with depression of miR-29b, whose existence restricts the development and incursion of cancer cells, with the potential interaction of interferon-γ (IFN-γ), IRF1, and IGF1 80 .…”
Section: Biological Functions Of Mirna In Cancermentioning
confidence: 99%
“…The angiogenesis of tumors can be controlled by miRNAs such as miR-210 and miR-519c under hypoxic conditions via modulating Hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) 78 . Regulatory networks of miRNAs are considered to be a characteristic of epithelial-mesenchymal transition (EMT) in the physiopathology of OSCC 79 . An aggressive phenotype of colorectal cancer (CRC) is significantly associated with depression of miR-29b, whose existence restricts the development and incursion of cancer cells, with the potential interaction of interferon-γ (IFN-γ), IRF1, and IGF1 80 .…”
Section: Biological Functions Of Mirna In Cancermentioning
confidence: 99%
“…Cancer malignant progression is determined by both endogenous changes of oncogenes and/or suppressors, and its surrounding tumor microenvironment (TME) . In the aspect of cancer cells, EMT is a complicated reprogramming process, which is characterized by the inhibition of epithelial markers and upregulation of mesenchymal markers . Therefore, we used multiple methods to evaluate the effects of miR‐30e‐5p on the alterations of EMT markers.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that miRNA play key roles in diverse biopathological behaviors, including malignant growth, metastasis and resistance to chemotherapy and radiotherapy . Abundant studies have shown that miRNA are dysregulated in numerous cancers, including SCCHN, contributing to cancer progression . Therefore, modulation of specific miRNA activities represents a potential therapeutic avenue …”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is the most common epithelial cancer of the head and neck [37,38]. OSCC is highly malignant and prone to local invasion and cervical lymph node metastasis, causing facial deformity, speech and esthetic disorders and leading to low survival rate and poor quality of life [38].…”
Section: Exosomes In Oral Squamous Cell Carcinomamentioning
confidence: 99%